2021
DOI: 10.1101/2021.11.22.469481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

All-optical electrophysiology with improved genetically encoded voltage indicators reveals interneuron network dynamics in vivo

Abstract: All-optical electrophysiology can be a powerful tool for studying neural dynamics in vivo, as it offers the ability to image and perturb membrane voltage in multiple cells simultaneously. The “Optopatch” constructs combine a red-shifted archaerhodopsin (Arch)-derived genetically encoded voltage indicator (GEVI) with a blue-shifted channelrhodopsin actuator (ChR). We used a video-based pooled screen to evolve Arch-derived GEVIs with improved signal-to-noise ratio (QuasAr6a) and kinetics (QuasAr6b). By combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Thus, fluorescent calcium signals are yet unable to resolve single action potentials (~ 1 ms), but rather serve as a proxy for events of neural activation. Recently, first studies using fluorescent voltage sensors have demonstrated proof-of-principle in rodent models and promise higher temporal resolution in future circuit studies ( Piatkevich et al, 2019 ; Tian et al, 2021 ). On the other hand, electrophysiological amplifiers can detect electrical signals on μs scale (filter frequency up to 20 kHz), exceeding the kinetics of the fastest ion channels and action potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fluorescent calcium signals are yet unable to resolve single action potentials (~ 1 ms), but rather serve as a proxy for events of neural activation. Recently, first studies using fluorescent voltage sensors have demonstrated proof-of-principle in rodent models and promise higher temporal resolution in future circuit studies ( Piatkevich et al, 2019 ; Tian et al, 2021 ). On the other hand, electrophysiological amplifiers can detect electrical signals on μs scale (filter frequency up to 20 kHz), exceeding the kinetics of the fastest ion channels and action potentials.…”
Section: Discussionmentioning
confidence: 99%
“…68 A preprint also recently reported using a similar approach to screen ∼120 000 single cells for voltage indicators with increased brightness and response amplitude, in this case using a green-to-red photoconvertible FP for optical tagging. 69 A key benefit of microscopy-based pooled screening compared with multiwell-based screening is the much higher achievable throughput. For example, multiwell-based screening of 3 million variants, the number of YFPs variants we screened to develop mGold, would require screening four 96-well plates per day for 21 years (assuming one variant per well and screening four plates per day).…”
Section: ■ Automating Multiwell Plate Screeningmentioning
confidence: 99%
“…Three million single-cell variants expressed in yeast were screened using SPOTlight, leading to the identification of a bright and photostable yellow fluorescent protein (YFP) variant called mGold that is 4–5-fold more photostable than its predecessor . A preprint also recently reported using a similar approach to screen ∼120 000 single cells for voltage indicators with increased brightness and response amplitude, in this case using a green-to-red photoconvertible FP for optical tagging …”
Section: Automated Microscope-based Pooled Library Screeningmentioning
confidence: 99%
“…Extracellular methods, such as multi-electrode arrays, field recordings, and wide-scale imaging of fluorophores overcome this limitation, but do not reveal which neurons are coupled in a network or the strengths or spatial distributions of their coupling. One could hope that cell-specific optogenetics could mitigate the barrier ( Dakin and Li, 2006 ; Qiao and Sanes, 2016 ), and some all-imaging approaches have identified GJ-mediated signals ( Tian et al, 2021 ). In computational studies of neural networks, electrical synapses are most often neglected entirely, which we regard as a vast missed opportunity.…”
Section: Introductionmentioning
confidence: 99%